Properties of appropriately and inappropriately expressed sodium channels in squid giant axon and its somata - Gilly, WF (J Neurosci, 1989)
Neurons that form the giant axons in squid by axonal fusion in the stellate ganglion are inexcitable and do not express functional voltage- controlled sodium (Na) channels in their somata in vivo. These cells do express Na channels in the soma membrane in vitro, however, provided they have been axotomized. We describe here voltage-clamp experiments on the isolated cell bodies maintained in primary culture and on acutely isolated giant axons designed to compare the functional properties of the Na channels expressed inappropriately in the soma with those of channels expressed normally in the axon. Approximately 85% of Na channels in the soma are essentially indistinguishable from those in the giant axon with regard to gating properties and sensitivity to tetrodotoxin or saxitoxin. Thus, the isolated soma is capable of processing Na channels to a state of apparent functional perfection. In addition to these normal Na channels, another type is regularly expressed in the cultured somata. This second type lacks inactivation and is preferentially sensitive to block by cadmium ions, but is otherwise indistinguishable from the more prevalent normal type of channels.